SYNTHESIS AND CHARACTERIZATION OF ZSM-5 MESOPOROUS WITH VARIATION RATIOS OF SiO2/Al2O3 - Susi Nurul Khalifah; Didik Prasetyoko (Jurnal Zeolit Indonesia, 2008)
ZSM-5 Mesoporous with variation ratios of SiO2/Al2O3 20, 35, 50, and 100 have been successfully synthesized. Phase of mesoporous created using Cetyltrimethylammonium bromide (CTABr) templates. Crystal obtained has an acidity and higher thermal stability. Diffraction peaks typical of ZSM-5 appeared at 2Î¸ = 7-9 ° and 2 Î¸ = 23.02 °, while typical peak of mesoporous materi als appeared on 2Î¸